2007
DOI: 10.1007/s00405-007-0410-1
|View full text |Cite
|
Sign up to set email alerts
|

Head and neck reconstruction with free flaps: a report on 213 cases

Abstract: The aim of this retrospective study is to review the experience of our institution in performing microvascular head and neck reconstruction between 2000 and 2004. During this period, 213 free flaps, including 146 radial forearm free flaps, 60 fibular flaps and 7 scapular flaps, were performed. Free flap success rate and complications were reported. The pre-treatment factors influencing these results were subsequently analyzed. Functional and aesthetic outcomes were evaluated by the same clinician. There were 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
68
2
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(81 citation statements)
references
References 79 publications
7
68
2
4
Order By: Relevance
“…The literature suggests differences in functional outcome after about 5 years because problems related to radiotherapy, like osteoradionecrosis, tooth decay, and dry mouth are aggravated over time (Tschiesner et al 2011;Nordgren et al 2008). In contrast, surgical reconstructions are assessed more positively by patients after about 6-12 months after reconstruction, probably due to improved swallowing and adaption of patients to the restoration of functions by the (Dassonville et al 2008;Wong and Wei 2010). It is planned to perform further prospective studies to investigate the influence of physiological therapies for patients undergoing surgical and radiation therapies to try to improve oral function, the overall mobility in the head and neck area, and the overall quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…The literature suggests differences in functional outcome after about 5 years because problems related to radiotherapy, like osteoradionecrosis, tooth decay, and dry mouth are aggravated over time (Tschiesner et al 2011;Nordgren et al 2008). In contrast, surgical reconstructions are assessed more positively by patients after about 6-12 months after reconstruction, probably due to improved swallowing and adaption of patients to the restoration of functions by the (Dassonville et al 2008;Wong and Wei 2010). It is planned to perform further prospective studies to investigate the influence of physiological therapies for patients undergoing surgical and radiation therapies to try to improve oral function, the overall mobility in the head and neck area, and the overall quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…The vascular pedicle is reliable, and in Dassonville et al's study there were no instances of necrosis, even partial, of the scapular flap. 6 Another valuable attribute of the parascapular flap is the ability of the flap to be used as a fasciocutaneous or osteocutaneous flap. 7 Although our study included only patients with fasciocutaneous flaps, a study by Coleman et al detailing the morbidity of osteocutaneous flaps revealed minimal decrease in range of motion, minimal decrease in strength, and no decrease in appearance.…”
Section: Case Reportmentioning
confidence: 99%
“…Disadvantages of free flap are failure (12,13). However, free flap transfer cannot be used for all patients at every institute since it requires special techniques and equipment's for microsurgery (7, 9 and 10).…”
Section: Introductionmentioning
confidence: 99%